Prevalence of diarrhea and its associated risk factors in children aged 1–60 months at Aba, South East Nigeria - Onyearugha, Chukwuemeka Ngozi; Okoronkwo, Nneka Chioma; Onyemachi, Prince Ezenwa (Eastern Journal of Medical Sciences, 2020)
Background: Diarrhea is a major cause of childhood morbidity and mortality worldwide, particularly in low resource nations. To achieve the Sustainable Developmental Goal 3.2, effective steps should be taken to stem the tide of childhood diarrhea and its associated mortality. Objective: The objective of the study was to determine the prevalence of diarrhea and its associated risk factors in children aged 1–60 months presenting to our health facility. Materials and Methods: In the present retrospective study, we reviewed medical records of children aged 1–60 months with diarrhea admitted to the Children Emergency Room and Pediatric Medical Wards of the Abia State University Teaching Hospital, Aba, from January 1, 2015 to December 31, 2016. Results: The prevalence of diarrhea was 11.2%. The study consisted of 68 males and 32 females with male:female ratio of 2.1:1. Around half (53%) of the children belonged to the age group of 1–12 months, 40% in the age group of 13–36 months, and 7% children belonged to the age group of 37–60 months. Most of the cases (88%) reported of acute watery diarrhea. The greatest monthly prevalence was in February (47%). Mortality rate was 22% which was significantly more among the infants, than among the age groups of 13–24 months and 25–36 months, respectively (p=0.019). Conclusion: The prevalence and mortality rates of diarrhea in this study were high. The mortality was significantly more among infants. Curbing the mortality of diarrhea in the under-five age group requires adopting specific measures to prevent and manage diarrhea, with special focus on infants.